A Simplified Irrigation Pump Testing Method for Developing Countries: A Case Study in Bangladesh†. (31st July 2018) - Yu, Su; Colton, Jonathan S.; Matin, Md. Abdul; Krupnik, Timothy J.
Abstract: Much of South Asia experiences a monomodal rainfall pattern with a distinct dry season following the annual monsoon. Enabling irrigation during the dry season has therefore been crucial in assuring improved productivity and double‐cropping. This is particularly the case in southern Bangladesh, where recent government initiatives have called for an expansion of surface water irrigation to reduce pressure on groundwater tables in intensively cultivated areas in the north of the country, where dry season boro rice is grown. This paper describes a method based on first principles of fluid mechanics to characterize the performance of surface water irrigation pumps used by small‐scale farmers in South Asia and Bangladesh. This method is unique, as it incorporates an optimized protocol suitable for resource‐limited conditions found in many developing countries and provides a comprehensive yet simple‐to‐use pump selection method for surface water irrigation pump customers. Using pump impellers as a case study, the method also characterizes the effect of pump geometric variations resulting from the variable production and assembly practices found in different manufacturing workshops. This method was validated with a case study in Bangladesh supported by both full‐scale field testing and numerical simulation results. © 2018 The Authors. Irrigation and Drainage published by John Wiley & Sons Ltd on behalf of International Commission for Irrigation and Drainage